AB0682 The incidence rate of inflammatory myopathies in slovenia. (15th June 2017) - Rotar, Ž; Hočevar, A; Krošel, M; Praprotnik, S; Tomšič, M
Abstract : Background: Annual incidence rates of inflammatory myopathies (IM) vary widely from 1.16–19.0 per 10 6 of adults.1 Our aim was to, for the first time, determine the incidence rate of IM in our population. Objectives: To determine the incidence rate of IM in our population. Methods: We retrospectively collected incident cases of IM from 1 January 2005 to 31 December 2016 at our department of rheumatology which is a part of an integrated secondary/tertiary university teaching hospital that is the only referral center for two well defined regions representing roughly a third of the national adult population. Tertiary cases are referred to our department from the entire country. We identified the cases by searching the electronic patient records (PRs) for ICD-10 codes M05, M33–35, M60, G73.7, G72.4. The paper and electronic PRs were scrutinized to assess clinical, laboratory and histopathological data. Descriptive statistics was used to describe our group of patients. The adult population size of the two regions served by our department was obtained from the national statistics institute database. The annual incidence rate for IM was then calculated. Results: During the 12-year observation period we identified 117 new cases of IM from a well-defined adult white Caucasian population aged 18 or above. 38 cases were excluded from analyses since they were referred to our department from outside the two regions we serve on the secondary and tertiary level. Thus, we analyzed 79 cases of IM (63% female; median (IQR) age 67 (55–75) years; 44% ever smokers). The median time to diagnosis was 5 (IQR 3–12) months. We diagnosed 29% patients with dermatomyositis, 25% with anti-synthetase syndrome, 18% with polymyositis, 9% with statin induced necrotizing autoimmune myopathy, 9% with concomitant myositis as a part of connective tissue disease, 6% with paraneoplastic myositis, and 4% with undifferentiated myositis. The IM cases were most often diagnosed in the summer months (32.9%), followed by spring (24.1%), fall (22.8%), and winter (20.3%). The clinical and laboratory characteristics at presentation are shown in Table 1 . Muscle biopsy was performed in 93% of patients. Notably, patients with swallowing difficulties had more commonly had Raynaud phenomenon (RR 3.7 (95% CI 1.4–9.4), p=0.008). Conclusions: The averaged 12-year annual incidence of IM in the population under study was 9.4 (95% CI 7.5–11.8) per 10 6 adults. References: Meyer A, et al. Rheumatology 2015. Disclosure of Interest: None declared